AWARE-P: A software for urban water infrastructure planning - Coelho, S. T. (2013)
High levels of deferred maintenance and rehabilitation and overwhelming investment needs in urban water services infrastructure demand wise spending and innovative, efficient planning. Rather than component-centric AM approaches, such as like-for-like prioritization and replacement, the complexity of the problem must be addressed by system-centric methods that ensure the best possible compromise between performance (level-of-service), risk and financial effort. An open-source software system based on a set of tools and models that assist in the analyses and decision support involved in the planning process has been developed in order to host the methods mentioned above. This paper presents the methodology and the software’s objectives and features, describes the context and vision that led to its inception and details the main design requirements and technology options.